2013
DOI: 10.2176/nmc.53.148
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Clipping of Bilateral Middle Cerebral Artery Aneurysms Via the Bilateral Pterional Keyhole Approach

Abstract: Five patients aged 55 to 73 years (mean 63 years) underwent one-stage clipping for unruptured aneurysms in the bilateral middle cerebral arteries (mean size 4.5 mm, range 2 to 7 mm) via the bilateral pterional keyhole approach in our institute. Important points are as follows: the head is affixed with no rotation; one side manipulation is started 5 minutes after the other side to avoid conflict of surgical instruments; a 5-cm curvilinear skin incision is made inside the hairline and pterional keyhole craniotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…For each type of approach it is extremely important to pay attention to several preconditions in order to perform them safely and effectively. [3,4,6,7] Single stage surgery has the advantages of removing a new risk of bleeding, curative treatment with one-time risk of general anaesthesia, shorter hospital stay and reduced cost in terms of bed charge, investigations and operative expenditure. [3,4,6,7] The most important reason for single stage surgery by bilateral approach is to eliminate the risk of bleeding from unruptured aneurysm in the early or late postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For each type of approach it is extremely important to pay attention to several preconditions in order to perform them safely and effectively. [3,4,6,7] Single stage surgery has the advantages of removing a new risk of bleeding, curative treatment with one-time risk of general anaesthesia, shorter hospital stay and reduced cost in terms of bed charge, investigations and operative expenditure. [3,4,6,7] The most important reason for single stage surgery by bilateral approach is to eliminate the risk of bleeding from unruptured aneurysm in the early or late postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,6,7] Single stage surgery has the advantages of removing a new risk of bleeding, curative treatment with one-time risk of general anaesthesia, shorter hospital stay and reduced cost in terms of bed charge, investigations and operative expenditure. [3,4,6,7] The most important reason for single stage surgery by bilateral approach is to eliminate the risk of bleeding from unruptured aneurysm in the early or late postoperative period. Two important large studies have showed that associated aneurysm in patients with SAH due to another ruptured aneurysm presents a higher risk for future bleeding than makes aneurysms of similar size with no SAH history [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations